2023
DOI: 10.1016/j.prosdent.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Association between obstructive sleep apnea and periodontitis in Chinese male adults: A cross-sectional study

Abstract: Obstructivesleep apnea (OSA), characterized by periodic and repetitive collapse of the upper airway during sleep, is a common disease with an estimated prevalence of 3% to 7% worldwide. 1 Patients with OSA undergo apnea and/or hypopnea, resulting in hypoxia, hypercapnia, sleep fragmentation, increased sympathetic activity, and altered immunity. 2,3 According to the American Academy of Sleep Medicine's (AASM) clinical practice guidelines, the management of patients by dentists through oral prosthesis therapy is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The search strategy initially recovered 265 citations. After excluding duplicates, as well as those not meeting the inclusion criteria, a total of 10 studies containing 30,994 participants were finally included ( 7 - 10 , 18 - 23 ). The search results have been represented in a flow diagram as per the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) guideline (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The search strategy initially recovered 265 citations. After excluding duplicates, as well as those not meeting the inclusion criteria, a total of 10 studies containing 30,994 participants were finally included ( 7 - 10 , 18 - 23 ). The search results have been represented in a flow diagram as per the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) guideline (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The agreement between the investigators for the eligibility judgment was excellent (Kappa statistic=0.88). Three studies had a high quality ( 8 , 10 , 21 ) and seven studies had a moderate quality ( 7 , 9 , 18 - 20 , 22 , 23 ). The baseline characteristics, as well as quality assessment, of the included papers have been summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported a significant association between SDB and periodontitis ( 17 , 25 , 26 ). An observational study found that the risk of periodontitis in patients at high risk of OSA was approximately double that at low risk of OSA ( 27 ).…”
Section: Introductionmentioning
confidence: 99%